English Language Communicative Competence and Learning Engagement of Senior High School Learners: Basis For Language Instructional Pocket - Prof. Resty C. Samosa; Stefhany Balasta; Rose Ann Elizabeth Halili; Jeancel Pineda; Maria Cassandra Silva (Peerian Journals Publishing, 2021)
The aim of the current study is to assessed the English language communicative competence and learning engagement of senior high school learners in selected Private Senior High School in the Schools Division of City of San Jose del Monte, Bulacan. Descriptive evaluation research was utilized to evaluate the influence, impact, or results of any practice, policy, or program. The respondents of the study were purposively selected which compromised to fifty (50) students and five (5) teachers that are teaching English language in selected private schools in the City of San Jose Del Monte, Bulacan. The researchers used the structured questionnaire which was a researcher- made instrument with 5- Likert scale survey. Data were analyzed using descriptive and inferential statistics. The findings showed that the level of English language communicative competence as assessed by teachers and learners was very satisfactory. On the other hand, the level of English language communicative competence of the learner in terms of linguistic competence, sociolinguistic competence and discourse competence have no significant difference. However, that strategic competence significantly differed when the teacher and learners assess it. In a way, the learners’ engagement was highly engaged in the English language communication as described in the three indicators of learners’ engagement. More than, that there is high positive correlation between English language communicative competence and learning engagement in the English language communication. Moreover, the learners’ shows highly encountered challenge in English language communication. Based on the foregoing conclusion, it is recommended that the module created by the researchers be used in their English classes since the topics included in the module were relevant to the actual findings. It is important for the different school administrators to ensure that the teachers are able to carry out the suggested topics included in the module.
Keywords: English language communicative competence; learning engagement; language instructional pocket; senior high school learners